A robust force feed-forward observer for an electro-hydraulic control loading system in flight simulators. (June 2019) - Zhao, Jinsong; Shen, Gang; Yang, Chifu; Zhu, Weidong; Yao, Jianyong
Abstract: A robust feed-forward observer is proposed for feel force control of an electro-hydraulic control loading system in flight simulators. Combining a velocity feed-forward compensator, the proposed control structure can effectively reduce a disturbance force caused by the control displacement of a pilot to further improve control performances. The electro-hydraulic control loading system is described as a force–displacement impedance system, including a mechanical system and a hydraulic control system, and its dynamic model is established as a double-loop system. Implementation of the proposed controller includes observer model design and filter optimization. Aiming at a force closed-loop which is always a non-minimum-phase system, an effective design method of an approximated inverse model is presented for obtaining an observer model, and it is an biregular transfer function. With the particular observer model, an optimization for the filter of feed-forward observer structure is carried out, by transforming  the original structure into a control structure with consideration of modeling error between the obtained observer model and the actual inverse model, which is a 2-independent-controllers structure. Then, an H ∞  controller is employed to optimize the transformed structure to indirectly obtain an optimized filter. In order to ensure existence of the H ∞  controller for the transformed structure of the feed-forward observer with a biregular observer model, some dynamic characteristics are analyzed and proved. Based on the characteristics, a nominal model modification method is presented to obtain a well-posed  H ∞  control structure. For designing a performance weighting function, an optimize goal is discussed and its proof is given, and then an algorithm using a bisection method is proposed to further improve the robust performance of the proposed controller. To verify the efficiency of the proposed controller, control performances of the electro-hydraulic control loading system are evaluated in experiments and are compared with those of other controllers, including the proportional–integral–derivative controller, the velocity feed-forward compensator, and the H ∞  controller. Experimental results show that the proposed controller can effectively reduce the disturbance force of the electro-hydraulic control loading system, and its impedance characteristics are closer to the ideal force feel model than the other controllers. Highlights: A robust feed-forward observer control and its optimization are presented. Characteristics of the control are studied for existence of an optimal solution. For the well-posed problem, the nominal model modification is proposed. A numerical-optimization is proposed for the performance weighing function.